Psychological Features of Attitude towards Health and Violation of Healthy Lifestyle in Russian University Students - Anna N. ZAKHAROVA; Evgeny L. NIKOLAEV; Denis V. HARTFELDER; Galina S. DULINA; Elena Yu. LAZAREVA; Tamara V. TALANOVA (Communications of International Proceedings, 2020)
The problem of responsibility of own health, health of other people, healthy lifestyle and prevention of health-related problems are important topics in modern society as health is determined by both current state of the healthcare system and personal attitudes towards one's health. With the spread of the covid-19 pandemic, it is becoming more and more relevant to study the attitude to health of various population groups and behavioral practices to maintain a healthy lifestyle. Nowadays health depends not only on the state of healthcare but also on the psychological characteristics and person's attitudes towards health. Therefore, finding differences in health attitudes among various socio-economic and age groups could provide more efficient approaches to health preservation among individuals and in society, which in turn requiring more studies of students' health preservation behavior management in educational organizations from psychological perspective. In this study, psychological characteristics of health and healthy lifestyle attitudes among state university students were studied. Total of 177 participants (49 male and 128 female students aged 18 - 41) had participated in the study. The article highlights results of these students obtained with Attitude towards health questionnaire (Berezovskaya R.A., 2005) and Violation of healthy behavior questionnaire (Lutzenko E.L. & Gabelkova O.E., 2013). The major question of the study was the effect of educational form on attitude towards health and specific healthy behavior violations, as well as which of these forms has the greatest potential for developing and maintaining healthy behavior of students. The results of comparative analysis of full-time and extramural students are provided.
Keywords: University students; health attitude; psychological characteristics; healthy lifestyle disorders; age differences; extramural and full-time education differences.